If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + 4c + 7x = 3(6x + -12) + -4(X + -6) Reorder the terms: 6 + 4c + 7x = 3(-12 + 6x) + -4(X + -6) 6 + 4c + 7x = (-12 * 3 + 6x * 3) + -4(X + -6) 6 + 4c + 7x = (-36 + 18x) + -4(X + -6) Reorder the terms: 6 + 4c + 7x = -36 + 18x + -4(-6 + X) 6 + 4c + 7x = -36 + 18x + (-6 * -4 + X * -4) 6 + 4c + 7x = -36 + 18x + (24 + -4X) Reorder the terms: 6 + 4c + 7x = -36 + 24 + -4X + 18x Combine like terms: -36 + 24 = -12 6 + 4c + 7x = -12 + -4X + 18x Solving 6 + 4c + 7x = -12 + -4X + 18x Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + 4c + -6 + 7x = -12 + -4X + -6 + 18x Reorder the terms: 6 + -6 + 4c + 7x = -12 + -4X + -6 + 18x Combine like terms: 6 + -6 = 0 0 + 4c + 7x = -12 + -4X + -6 + 18x 4c + 7x = -12 + -4X + -6 + 18x Reorder the terms: 4c + 7x = -12 + -6 + -4X + 18x Combine like terms: -12 + -6 = -18 4c + 7x = -18 + -4X + 18x Add '-7x' to each side of the equation. 4c + 7x + -7x = -18 + -4X + 18x + -7x Combine like terms: 7x + -7x = 0 4c + 0 = -18 + -4X + 18x + -7x 4c = -18 + -4X + 18x + -7x Combine like terms: 18x + -7x = 11x 4c = -18 + -4X + 11x Divide each side by '4'. c = -4.5 + -1X + 2.75x Simplifying c = -4.5 + -1X + 2.75x
| 5*(5d+6)= | | 4y+1=3y-1 | | Sqrt(x^2+6)+sqrt(7x)=0 | | 5(1+3m)=10(X-1) | | 9(f+6)= | | 6*(3a+b)= | | 5e+7= | | 56=1/2b(14) | | 1011=5 | | -16x^2+15x-88=0 | | -9+2=18 | | 2y-3(5y-1)=3-4(1-y) | | 3(X-7)=3(3-9n) | | sinx=5/2 | | 552.8(-0.1)= | | 4+494736382= | | 2a+2a^2=84 | | 12x+40=184 | | 10/2x=5x | | 3(2x+5)=333 | | 7x^2+12x+8=5x^2+7x+8 | | f(x)=sqrt(2x+1) | | -1÷2/4= | | 9x-8(x-9)+7(y-9)= | | 12x^2-24x+12= | | -1÷2/4 | | 8x-14=8x | | (9ab/10b^3)*(2b/3a) | | b2-4/2=10 | | 4/5x-214 | | m^2-4m=5m-8 | | 13/m=2/9 |